Lost to follow-up – who, why and what can be done?. (4th April 2011) - Cifelli, A; Parkes, S; Davies, P; Jenkinson, H
Abstract : Aims: It is well recognised that following completion of treatment for childhood malignancy, a number of patients become 'lost to follow-up' (LTF). These patients and their primary care physician may be unaware of their long term health risks and as a consequence may experience adverse health outcomes and greater morbidity or even mortality. This study aimed to investigate the administrative, medical and psychosocial factors which may contribute to a patient becoming LTF. Methods: A cohort of survivors of childhood cancer was identified using a regional, population based long term follow-up (LTFU) database. For each patient, all available data including medical records, hospital administrative systems and past correspondence were used to obtain information on diagnosis, treatment, demographic and social factors, age at diagnosis, date when last seen and number of known late effects identified at previous out-patient appointments. Results: 1814 patients, treated for childhood cancer at one institution between 1964 and 2005, were registered on the LTFU database. 427 of these patients had become LTF and the remaining 1387 were still attending follow-up clinics. 27% of leukaemia survivors had become LTF compared with only 17% of brain tumour survivors. Morbidity data indicated that patients who were LTF had significantly fewer long term problems than those still attending (p<0.001). The median interval from diagnosis to cessation of attendance was 13 years, the majority of these patients being within the 17–25 age group at cessation. There were no differences in psychosocial and demographic factors between the LTF and 'attending' groups. No effects of time were noted. In addition, hospital administration systems may have been responsible for up to 40% of patients lost. Conclusions: This study has highlighted the multi-factorial nature of non-attendance at clinic. Although it is eassuring that the patients with the greatest clinical need are still attending clinic, it is hoped that this may provide an impetus to consider alternative, flexible, more user-friendly models of LTFU care especially for lower risk patients. Awareness of the age at which patients become 'lost' will enable targeted intervention programmes to be implemented around the time of adolescence and transition.